Add-on effect of the Guizhi Fuling formula for management of reduced fertility potential in women with polycystic ovary syndrome: A systematic review and meta-analysis of randomized controlled trials - Rong, Anna; Ta, Na; E., Lihua; Meng, Wenbin (Frontiers in Endocrinology, 2023)
Background: Guizhi Fuling (GZFL) pill, a traditional Chinese herbal formula including Semen Persicae, Ramulus Cinnamomi, Poria, Radix Paeoniae Alba, and Cortex Moutan, has been widely applied in the management of gynecological diseases. Objective: To evaluate the add-on effect of GZFL formula for treating reduced fertility potential in women with polycystic ovary syndrome (PCOS) by conducting a systematic review and meta-analysis. Methods: Two reviewers independently searched PubMed, Embase, Cochrane Library, Wanfang, SinoMed, and CKNI databases until December 9, 2022. Eligible studies were randomized controlled trials (RCTs) of GZFL formula plus Western medicine versus Western medicine for treating PCOS. The primary endpoint was the ovulation, pregnancy, and miscarriage rate. The secondary endpoints included the serum follicle-stimulating hormone (FSH), total testosterone, luteinizing hormone (LH), estradiol, and homeostasis model assessment insulin resistance (HOMA-IR). Results: Sixteen RCTs with 1385 patients were identified. GZFL formula plus Western medicine significantly improved ovulation rate (risk ratios [RR] 1.24; 95% confidence intervals [CI] 1.15–1.34) and pregnancy rate (RR 1.53; 95% CI 1.38 to 1.69) than the Western medicine alone. Adjuvant treatment with GZFL formula also significantly decreased the serum FSH (mean difference [MD] -0.48 U/L; 95% CI -0.80 to -0.15), total testosterone (standard mean difference [SMD] -1.07; 95% CI -1.71 to -0.44), LH level (MD -2.19 U/L; 95% CI -3.04 to -1.34) and HOMA-IR (MD -0.47; 95% CI -0.60 to -0.34). However, there was no significant difference in miscarriage rate (RR 0.89; 95% CI 0.36–2.20) and serum estradiol level (SMD 0.34; 95% CI -0.25 to 0.94) between two groups. Conclusions: GZFL formula as adjuvant therapy can improve ovulation and pregnancy rate in women with PCOS. Its beneficial effects may correlate with reducing FSH, total testosterone, LH, and ameliorating insulin resistance. However, more well-designed RCTs with larger samples and multi-center trials are required to confirm the current findings due to uncertainty of the evidence.